Factors related water and dry matter during pre- and post- heading in four millet species under severe water deficit. (2nd January 2020) - Matsuura, Asana; An, Ping
ABSTRACT: The objectives of this study are to clarify the relative importance of sink and related factors of dry matter and water use pre-and post-heading in four millet species under severe water deficit. Panicum miliaceum, Panicum sumatrense, Setaria glauca ., and S. italica were used. Water deficit (20% soil water content) was imposed from 25 d after sowing until harvest, with 40% soil water as a control. At the heading, half of the leaf area or all leaves on each plant were removed in both the control and the water deficit treatment (Source manipulation). Water deficit treatment markedly decreased the leaf water potential of all species from −2.02 MPa ( S. italica ) to −1.72MPa ( P. miliaceum ). The grain yields of water deficit treatment in S. italica, P. miliaceum, S. glauca and P. sumatrense decreased to 62, 48, 31, and 24% of the control, respectively. Four millet species were divided to dehydration-tolerant millet ( S. italica and P. miliaceum ) and dehydration-susceptible millet ( S. glauca and P. sumatrense ) by calculating drought susceptibility index. The interspecific difference in dehydration tolerance was accounted for by the number of grains per panicle and the harvest index. The source operation showed that the sink was more important than the source. In conclusion, under severe soil drying, it was considered that S. italica and P. miliaceum showed strong dehydration tolerance because they maintained the number of grains per panicle and did not reduce dry matter production and the partitioning of dry matter to the panicle after heading. Abbreviations: CLA0: all leaves were removed at heading in the control; CLA0.5: half of the leaf area per plant was removed at heading in the control; DAS: days after sowing; DLA0: all leaves were removed at heading in the dehydration treatment; DLA0.5: half of the leaf area was removed at heading in the dry treatment; DSI: drought susceptibility index; NSC: nonstructural carbohydrate; OA: osmotic adjustment; WUE: water use efficiency. Graphical abstract: